Appreciation of Interprofessional Perspectives: A Standardized Patient Experience to Promote Communication Between Nursing and Medical Students - Amy Lawson; Heather Hageman; Beth Rotter; Gail Rea; John Kirby; Angela McConachie; Robert Rothbaum (Association of American Medical Colleges, 2013)
Abstract Introduction Team-based training often does not occur until after completion of the undergraduate curriculum. Thus, trainees are often ill-equipped to manage team-based care when beginning the next phase of their education. In recognition of this gap in training, we developed this interprofessional simulation experience. Methods This simulation experience consists of 90-minute sessions, held three times a year, in which pairs or teams of medical and nursing students complete two standardized patient cases and a debriefing session. During the standardized patient session, each team saw two patients: knee replacement and post-appendectomy. Following the encounters, standardized patients completed a checklist that recorded student performance and students completed an experiential survey and presession attitudinal survey. A 30-minute student debriefing session followed both exercises. Results Our research found that nursing and medical students attitudes changed significantly in a majority of questions relating to teamwork, communication, scope of practice, and communication and collaboration in care plan development which may impact improved patient outcomes. Discussion Because this was the first time our medical students and nursing students had interacted, the students' informal conversations helped further our objectives. Students were heard discussing their course of training, future specialty choices, and many other topics. Keeping the atmosphere light and positive (as opposed to the exam conditions often in effect in the standardized patient suite) helped to further these interactions.